Real-Time Action - Krishnan, Padmanabhan (DAIMI Report Series, 1991)
The behaviour of a real-time system depends on the scheduler used. The order in which tasks are executed depends on its characteristics such as ready time, deadline etc. We describe a language in which the readiness and deadlines can be specified. A scheduling policy using the task characteristics can be defined. To study the effect of schedulers on a system a notation should allow for the specification of time, processes and scheduling. In this paper we show the applicability of the Action Notation for specifying real-time behaviour.